Can Wind Energy Continue Double-Digit Growth?. - Fairley, P.
The need for backup power has been overstated, but grid interconnections are crucial. Wind power supplies a large proportion of the electricity in countries like Denmark, Germany, and Spain, and its use is growing at an explosive pace around the world. Wind power's rapid growth, especially in Europe, is sustainable only if grid interconnections improve
Keywords: Denmark; Europe; Germany; IEA; International Energy Agency; Spain; Flows backup power; Grid interconnections; Investment; Overloads; Power-generation companies; Transmission capacity; Transmission lines; Unanticipated power flows; Wind energy; Wind farms; Wind power; Wind-tossed electric grids